Career orientations of students with disabilities - Elena V. Arzhanykh; V. V. Moysov (Высшее образование в России)
The paper describes the findings of the survey of students with disabilities of Moscow schools andtheir parents conducted by the Laboratory оf monitoring studies of the Moscow State University of psychology and education in autumn 2012. It contains data identifying the demand for higher education and professional orientations (preferences in the choice of occupation, level of education and professional school for further education).